(untitled) (Scientia Agricola, 2007)
In some regions where cotton is grown in Brazil rainfall amounts to about 2,000 mm per year, which imposes a great risk for Mepiquat Chloride (MP) to be washed from cotton leaves before being absorbed. The objective of this research was to evaluate the MC persistence when applied on cotton plants submitted to different rain intensities after spraying. The treatments were three MC rates: 0, 15.0 and 30.0 g a.i. ha-1 and four simulated rainfalls, applied 90 minutes after MC spraying: 5, 10, 20 and 40 mm, plus a treatment without rain. Cotton plants of the cv. Delta Opal were grown in 12 L pots filled with an Haplortox. The experimental design was consisted of complete randomized blocks, in a factorial scheme, with four replicates. The evaluated parameters were: plant height, number of reproductive branches, dry matter weight, reproductive structures, retention and leaf area. The higher the rainfall the lower the effectiveness of the plant growth regulator in controlling plant height. A simulated rainfall as low as 5 mm occurring 90 minutes after MC application was enough to wash some of the plant growth regulator from cotton leaves.